Modified Delphi Consensus to Suggest Key Elements of Stepping On Falls Prevention Program - Mahoney, Jane E.; Clemson, Lindy; Schlotthauer, Amy; Mack, Karin A.; Shea, Terry; Gobel, Vicki; Cech, Sandy (Frontiers in Public Health, 2017)
Falls among older adults result in substantial morbidity and mortality. Community-based programs have been shown to decrease the rate of falls. In 2007, the Centers for Disease Control and Prevention funded a research study to determine how to successfully disseminate the evidence-based fall prevention program (Stepping On) in the community setting. As the first step for this study, a panel of subject matter experts were convened to suggest which parts of the Stepping On fall prevention program were considered key elements, which could not be modified by implementers. Methods: Older adult fall prevention experts from the United States, Canada, and Australia participated in a modified Delphi technique process to suggest key program elements of Stepping On. Forty-four experts were invited to ensure that the panel of experts would consist of equal numbers of physical therapists, occupational therapists, geriatricians, exercise scientists, and public health researchers. Consensus was determined by percent of agreement among panelists. A Rasch analysis of item fit was conducted to explore the degree of diversity and/or homogeneity of responses across our panelists. Results: The Rasch analysis of the 19 panelists using fit statistics shows there was a reasonable and sufficient range of diverse perspectives (Infit MnSQ 1.01, Z score -0.1, Outfit MnSQ 0.96, Z score –0.2 with a separation of 4.89). Consensus was achieved that these elements were key: 17 of 18 adult learning elements, 11 of 22 programming, 12 of 15 exercise, seven of eight upgrading exercises, two of four peer co-leader’s role, and all of the home visits, booster sessions, group leader’s role, and background and training of group leader elements. The top five key elements were: 1) use plain language, 2) develop trust, 3) engage people in what is meaningful and contextual for them, 4) train participants for cues in self-monitoring quality of exercises, and 5) group leader learns about exercises and understands how to progress them. Discussion: The Delphi consensus process suggested key elements related to Stepping On program delivery. These elements were considered essential to program effectiveness. Findings from this study laid the foundation for translation of Stepping On for broad U.S. dissemination.